Bridging oxygen atoms in trigonal prism units driven strong second-harmonic-generation efficiency in Sr3Ge2O4Te3. Issue 79 (16th September 2022) - Sun, Mengran; Xing, Wenhao; Lee, Ming-Hsien; Yao, Jiyong
Abstract : A new IR NLO crystal Sr3 Ge2 O4 Te3 was successfully designed and synthesized by a "partial O-to-Te substitution" strategy. The bridging oxygen in [Ge2 Te3 O4 ] plays the most important role in the enhanced SHG effect of Sr3 Ge2 O4 Te3 . Abstract : Herein, a novel IR NLO oxytelluride Sr3 Ge2 O4 Te3 was successfully designed and synthesized through a "partial O-to-Te substitution" strategy. Compared with the parent oxide, Sr3 Ge2 O4 Te3 not only successfully achieves a phase-matchability transition (from NPM to PM), but also greatly improves the linear and NLO performances, including a wide band gap (2.26 eV), strong SHG response (1.3 × AgGaSe2 ) and large optical anisotropy (Δ n = 0.152@2090 nm). The analyses of the structure–property relationship and SHG-density indicate that the bridging oxygen in the [O3 Ge–O–GeTe3 ] prism unit plays the most important role in the multiplication SHG effect. This work provides some insights into the design and exploration of novel IR NLO materials.